The promoter polymorphisms of receptor for advanced glycation end products were associated with the susceptibility and progression of sepsis. Issue 4 (30th June 2016) - Shao, Y.; Shao, X.; He, J.; Cai, Y.; Zhao, J.; Chen, F.; Tao, H.; Yin, Z.; Tan, X.; He, Y.; Lin, Y.; Li, K.; et al.
Abstract : Abstract : Receptor for advanced glycation end products (RAGE) is considered a major pattern recognition receptor, which plays an important role in the development of sepsis. Increasing evidence showed an association between RAGE polymorphisms and the susceptibility to several inflammatory‐related diseases. However, little is known about the clinical relationship between RAGE polymorphisms and sepsis. In this study, we analyzed the association of sepsis with three functional RAGE gene polymorphisms (rs1800624, rs1800625 and rs2070600) in a Chinese Han population (372 sepsis cases and 400 healthy controls). Significant differences were observed in the rs1800624 and rs1800625 genotype/allele distributions between the sepsis and controls, but no significant difference was observed in the rs2070600 genotype/allele. Moreover, our results also revealed a significant difference in the genotype/allele frequencies of the rs1800624 and rs1800625 polymorphisms between the sepsis and severe sepsis subtypes, the rs1800624 TT or rs1800625 TT genotype carriers exhibited a significant increase in RAGE mRNA, sRAGE, TNF‐α and IL‐6 expression compared with the rs1800624 AT/AA or rs1800625 CT/CC carriers in sepsis patients. Overall, this study might provide valuable clinical evidence between the RAGE gene polymorphisms and the risk or the development of sepsis.